AS-ProCBE - An Architectural Model for Adaptive Security through Progressive Context-Based Enrichment - Almeida, Ricardo Borges; Machado, Roger da Silva; Donato, Lucas Medeiros; Yamin, Adenauer C.; Pernas, Ana Marilza (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2020: Proceedings of the 26th Brazilian Symposium on Multimedia and the Web, 2020)
The Internet of Things (IoT) is a Ubiquitous Computing materialization that is gaining prominence. Security has become potentialized as a necessary feature for a viable IoT. Promoting security over this dynamic and heterogeneous environment with pre-defined and static security mechanisms is an unfeasible task. Therefore, solutions for adaptive security are required. This paper has as main objective to present the conception of a proposal for adaptive security through progressive context-based enrichment considering the challenges of IoT scenarios, offering as a differential the contextual information acquisition in the opportune moment and contemplating heterogeneous sources. To evaluate this proposal was developed one case study to validate the progressive contextualization of security events. Finally, the strengths and limitations of our approach are discussed, followed by future works.